Flopping, Klapping and Gene Doping: Dichotomies between 'Natural' and 'Artificial' in Elite Sport - van Hilvoorde, I.; Vos, R.; de Wert, G. (Social Studies of Science, 2007)
The application of genetic technology seems to threaten what is considered natural in elite sport. This paper explores the role of genetic technology in elite sport and questions the significance of dichotomizing between the natural and artificial element. How do shifts in technology affect the attribution of the human element in athletic performance? To explore the attribution of human agency we compare the genetic enhancement of athletes with two other shifts of the 'natural performance' in sport: first, the introduction of a revolutionary high jump technique, the Fosbury flop, in 1968; and, second, the introduction of the klapskate in speed skating in 1997. The three cases show that artificiality as such can hardly be a criterion for evaluating processes of innovation. The context of elite sport is itself highly artificial. Boundaries between the natural body and the enhanced body are the outcome of institutional processes of boundary work. When discussing new technologies in sport it is better to ask if athletes are still playing the same game and whether or not there are equal opportunities and an equal distribution of means for playing the game. The introduction of gene technology may result in inequalities, with great impact on the outcome of the game. This outcome may be considered irrelevant for the inequalities that the game is supposed to produce and measure. Genetic enhancement may also threaten the public view of athletes as moral agents and possibly change the appreciation for human performance.